A Case Report on Efavirenz Induced Gynaecomastia - Rukmangathen, Rajalakshmi; Brahmanapalli, Vasundara Devi; Devulapalli, Meghana; Thammisetty, Durga Prasad; Bondalapati, Avanthi; Shaik, Shabana Banu; Bathula, Pavan Kumar (Indian Journal of Pharmacy Practice)
Gynaecomastia in simple terms means development of breast in the males. This may be associated with various clinical conditions in men depending on the age at the time of diagnosis and may be due to intake of certain drugs that have the potential to cause breast enlargement. In HIV positive individuals Antiretro viral agent’s intake was associated with development of breast tissue in males with efavirenz being one of such drugs. We report a case of efavirenz induced gynaecomastia in 37 year old male seropositive patient.
Keywords: Breast masses; Antiretroviral therapy; Drug induced gynaecomastia; Fine Needle Aspiration Cytology; Seropositive; Breast enlargement; Efavirenz; Gynaecomastia